Pengaruh Kepadatan Penduduk, Jumlah Tenaga Kerja, dan Indeks Pembangunan Manusia (IPM) Terhadap Produk Domestik Regional Bruto (PDRB) di Provinsi Jawa Tengah - Taswati Nova Wijayaningrum (AKUNTANSI 45, 2023)
GRDP per capita is often used as an indicator to measure the level of prosperity and level of development of a region. Economic inequality between provinces in Indonesia is high. Population density and HDI factors have a significant effect in modeling provincial GDP per capita, while the number of workers is not significant. Reducing population density on the island of Java, especially DKI Jakarta, as well as efforts to increase human development outside Java is predicted to be able to reduce economic inequality between regions. The aim of this research is to determine the effect of population density, number of workers, and HDI on GDP per capita in Central Java Province. The analytical method used is a quantitative approach using multiple linear regression analysis via SPSS software. The results of the analysis found that only HDI was significant for GDP per capita in Central Java Province. The variables population density and number of workers have a positive influence but are not significant because the significance value is > 0.05. This can be interpreted as if the people of a district/city tend to have a good quality of life (indicated by a high HDI value) then the GDP per capita in that district/city will also be relatively high. However, when viewed simultaneously or together these three variables have an influence on the formation of GRDP per capita in Central Java Province in 2022.